Pseudobulbar affect as a negative prognostic indicator in amyotrophic lateral sclerosis. (11th March 2018) - Tortelli, R.; Arcuti, S.; Copetti, M.; Barone, R.; Zecca, C.; Capozzo, R.; Barulli, M. R.; Simone, I. L.; Logroscino, G.
Abstract : Objective: To evaluate whether the presence of pseudobulbar affect (PBA) in an early stage of the disease influences survival in a population‐based incident cohort of amyotrophic lateral sclerosis (ALS). Methods: Incident ALS cases, diagnosed according to El Escorial criteria, were enrolled from a prospective population‐based registry in Puglia, Southern Italy. The Center for Neurologic Study‐Lability Scale (CNS‐LS), a self‐administered questionnaire, was used to evaluate PBA. Total scores range from 7 to 35. A score ≥13 was used to identify PBA. Cox proportional hazard models were used for survival analysis. The modified C‐statistic for censored survival data was used for models' discrimination. RECursive Partitioning and AMalgamation (RECPAM) analysis was used to identify subgroups of patients with different patterns of risk, depending on baseline characteristics. Results: We enrolled 94 sporadic ALS, median age of 64 years (range: 26‐80). At the censoring date, 65 of 94 (69.2%), 39 of 60 (65.0%), and 26 of 34 (76.5%) patients reached the outcome (tracheotomy/death), in the whole, non‐PBA and in the PBA groups, respectively. Kaplan‐Meier survival curves for the two subgroups were not significantly different (log‐rank test: 1.3, P  = .25). The discrimination ability of a multivariable model with demographic and clinical variables of interest was not improved by adding PBA. In the RECPAM analysis, ALSFRSr and the total score of CNS‐LS scale (</≥10) were the most important variables for differentiating all risk categories. Conclusions: These preliminary results underlie that the presence of PBA at entry negatively influences survival in a specific subgroup of patients with ALS characterized by less functional impairment.